Ethnic Conflict and Civic Life: Hindus and Muslims in India by Ashutosh Varshney (New Haven and London: Yale University Press, 2002. 382 pages.) (American Journal of Islam and Society, 2004)
While Ashutosh Varshney’s book, Ethnic Conflict and Civic Life: Hindusand Muslims in India, cannot be judged by its cover, it can be judged byits index. His exhaustive and erudite study of riots in India only includesa paltry three references to the Rashtriya Swayemsevak Sangh (RSS) andVishwa Hindu Parishad (VHP), two Hindu nationalist organizations thatplay a central role in such riots. He also fails to mention the Bajrang Dal,the militant Hindu organization responsible for many of the attacks duringthe violence in Gujarat in 2002. This seems to summarize the problemwith his book: It is intriguing yet incomplete.The reason for this omission becomes clear from his central thesis:Riots seldom occur where integrated networks of civic engagement exist;riots are a common feature where interdependency is absent. Varshney, aprofessor of political science at the University of Michigan, surveys sixcities in India: three riot-prone (Hyderabad, Ahmedabad, Aligarh) andthree riot-free (Lucknow, Calicut, Surat).His focus on India’s urban centers is not without reason. Only 4% ofcommunal violence-related deaths have occurred in rural areas, where67% of the Indian population lives. Eight cities (whose total populationis only 5% of the country’s total population) account for 45% of deaths incommunal violence. Varshney seems overly eager to correct the notionthat Hindu-Muslim violence is a pan-Indian experience.His book highlights some important divisions that contribute to interreligiousdiscord. In chapter 5, for example, he notes that Aligarh MuslimUniversity (AMU), once an educational center for both Muslims andHindus, is now largely a university exclusively attended by Muslims.Such divisions at the higher academic levels lead to inevitable cleavagesin society. Varshney concludes that “local patterns of violence underlinehow important associational ties across communities are for peace inmulti-ethnic societies” (p. 11).It is tempting to agree with Varshney. His book suggests the basicpremise that if Muslims and Hindus work together, they will not resort tocommunal violence. One can understand why his ideas have gained supportfrom government officials, apologetic Indian scholars, and ...